Microfluidics for Biomedical Applications - Xiang, Nan; Ni, Zhonghua (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on the most recent technical innovations and developments in the area of microfluidics, particularly in relation to their biomedical applications. The advent of microfluidics has provided important insights into the fields of biomedical research and clinical diagnosis. Special attention is given to the isolation and detection of circulating tumor cells and exosomes, the generation of concentration dilutions, the rapid sensing and detection of single molecules and viruses, and the innovations in inertial microfluidics, electrical impedance, magnetic biosensors, and droplet microfluidics.